The Cambridge Companion to Human Rights and Literature / Ed. - Parikh, Crystal (Singapore : Cambridge University Press, 2019)
"Literature has been essential to shaping the notions of human personhood, good life, moral responsibility, and forms of freedom that have been central to human rights law, discourse, and politics. The literary study of human rights has also recently generated innovative and timely perspectives on the history, meaning, and scope of human rights. The Cambridge Companion to Human Rights and Literature introduces this new and exciting field of study in the humanities. It explores the historical and institutional contexts, theoretical concepts, genres, and methods that literature and human rights share. Equally accessible to beginners in the field and more advanced researche[r]s, this Companion emphasizes both the literary and interdisciplinary dimensions of human rights and the humanities"--
Machine generated contents note: Chronology of major works and events, 1215-2018 Saronik Bosu and Heba Jahama; Introduction Crystal Parikh; Part I. Genealogies and Contexts: 1. Recounting history, locating precursors for human rights Sarah Winter; 2. Humanitarianism's way in the world: on missionary and emergency imaginaries Kerry Bystrom and Eleni Coundouriotis; 3. Literature, human rights and the Cold War Andrew Hammond; 4. Human rights in the vernacular: translating and inventing rights outside the state David Palumbo-Liu; Part II. Fashioning Methods: 5. Law and literature, the procedural and the performative Audrey J. Golden; 6. Human rights modes and media Lieve Gies; 7. Remembering the forgetting: human rights literature and memory work Cathy J. Schlund-Vials; 8. Queering human rights: the transgender child Wendy S. Hesford and Rachel A. Lewis; Part III. Generic Representations: 9. Narrating the human person Sunny Xiang; 10. The dramas of human rights: documentary theater and performance Brenda S. Werth; 11. Poetic justice and the idea of poetic redress Rajeev S. Patke; 12. Truth-telling: reportage and creative nonfiction James Dawes; 13. Visualizing the world: graphic novels, comics, and human rights Charlotte Salmi; Part IV. Writing Human Rights: 14. Perpetrators, victims, and beneficiaries: the subjects of human rights Elizabeth Swanson; 15. Routing emotions, forming humans: affect, aesthetics, rhetoric Greg A. Mullins; 16. Beyond sovereignty: reimagining vulnerability and security Alexandra S. Moore; Bibliography Saronik Bosu and Heba Jahama.
Keywords: Human Rights in Literature; Law in Literature; Social Justice in Literature; Humanitarianism in Literature